Pentingnya Kesadaran Masyarakat Terhadap Kekerasan: Strategi Webinar Dalam Perlindungan Dan Mekanisme Pengaduan Bagi Perempuan Dan Anak - Mutmainnah; Yenni Bilolo; Andi Farwatunnisa; Ainun Muflihah Yusuf; Muhammad Nur Hidayat Nurdin; Muhrajan Piara (CV. Multi Kreasi Media, 2023)
The prevalence of issues regarding violence against women and children has become a fairly popular topic in recent years. Violence against women and children in Indonesia continues to occur over time and takes on increasingly diverse forms. Therefore, the protection of women and children has become a primary focus of the Indonesian government. If not addressed seriously, the potential damage to the mental, moral, and spiritual well-being of the younger generation, including children considered as Indonesia's golden generation, may increase due to the significant impact of trauma. The method of implementing activities involves a webinar addressing the topic of